PENGARUH PENERAPAN APLIKASI KOPIKu ¨KONTRSEPSI PILIHANKU¨ TERHADAP PENGETAHUAN IBU HAMIL TRIMESTER 3 TENTANG KONTRASEPSI IUD - Meti Patimah; Sri Susilawati; Sri Wahyuni Sundari (Jurnal Ilmiah Kebidanan Imelda, 2022)
Healthy pregnancy preparation and pregnancy planning are important factors in preventing maternal and infant mortality rates, many programs have been launched by the government including the 1000 HPK program and family planning programs to regulate pregnancy. The low knowledge and level of education of women of childbearing age leads to low coverage of long-term contraceptives. ¨KOPIKu ̈ application is an android-based application that contains various contraceptive methods that are divided according to needs. The purpose of this study was to determine the effect of the application of ¨KOPIKu ̈ application on the knowledge of pregnant women in the 3rd trimester about IUD contraception. The subjects of the study were 3rd trimester pregnant women who had never used an IUD in the work area of the Karanganyar Health Center in Tasikmalaya City as many as 35 people. The research design used was a pre-post test design without control with influence analysis using a T-test. The results of the analysis of the average knowledge of respondents before being given the application were 52.63 while the average knowledge after being given the application was 84.40 and the results of the T test obtained a p value of <0.05. The application of the ̈KOPIKu ̈ application affects the knowledge of pregnant women in the 3rd trimester about IUD contraception.